SYSTEMIC EFFECTS OF UNIVERSITY COMPLEXES - N. O. Vaganova; V. M. Lopatkin (Образование и наука)
The aim of the present article is to reveal system effects of the university complexes including the organizations of professional education on different levels.Methodology and research methods. Theoretical methods: receipt of scientific information on systems, collection of data on university complexes; empirical: comparison and correlation of the obtained data.Results and scientific novelty. A university complex is designated as a system. The system effects being the results of integration of the organizations of professional education of different levels are educed: effect of instability of the hierarchical relations when preserving a certain structure of a university complex; effect of a single educational purpose, effect of influence of the external environment. These effects cause emergence of new quality of the integrated pedagogical system which is designated as «ability to self-regulating updating».Practical significance. The materials and results of the study can be used for further development of university complexes as organizations that integrate the establishments of vocational education on different levels.